Pour une approche identitaire en traduction : implications socio-culturelles - Żuchelkowska, Alicja (Wydawnictwo Naukowe UAM, 2012)
The objective of this text consists in presenting how it is necessary for contemporary translators and interpreters (both literary and specialised) to acquire and develop the ability to recognize elements of identity discourse in translated texts. Nowadays, the need for inter-cultural exchange is inevitably connected with the necessity of establishing harmonious co-existence for numerous cultures and identities. Therefore, it is crucial to educate translators in a way that enables them to pay special attention to identity and cultural perturbations present in translated texts (culture and language hybridisation, multiple identity, cultural dislocation, presence in linguistic and political discourse of minority cultures), regardless of their genre or form. Such a strong emphasis on identity problems in the translation is especially relevant in the European context, where the attention of researchers and politicians directed at identity problems stemming from ethnical and cultural issues sets the framework for a new cultural paradigm that determines the future development of the Eu. Becoming acquainted with this paradigm which emphasises fl uency, identity unmarkedness and the new model of European collectivity is indispensable for a translator aspiring to become a true cultural mediator.
Identity approach in translation : sociocultural implications
Keywords: Translation; Cultural and linguistic identity; Cultural and language hybridisation